2011
DOI: 10.1016/j.ijpharm.2011.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Comparative sensitivity of tumor and non-tumor cell lines as a reliable approach for in vitro cytotoxicity screening of lysine-based surfactants with potential pharmaceutical applications

Abstract: Surfactants are used as additives in topical pharmaceuticals and drug delivery systems.The biocompatibility of amino acid-based surfactants makes them highly suitable for use in these fields, but tests are needed to evaluate their potential toxicity. Here we addressed the sensitivity of tumor (HeLa, MCF-7) and non-tumor (3T3, 3T6, HaCaT, NCTC 2544) cell lines to the toxic effects of lysine-based surfactants by means of two in vitro endpoints (MTT and NRU). This comparative assay may serve as a new approach for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 41 publications
(55 reference statements)
2
35
1
1
Order By: Relevance
“…The choice of 77KS as a bioactive excipient in the NP formulation was based on our previous studies, which showed its pH-sensitive membrane-disruptive activity, together with improved kinetics in the endosomal pH range and low cytotoxic potential (Nogueira et al 2011a(Nogueira et al , 2011b. 77KS was incorporated into the NPs at a concentration below its CMC, thereby indicating that this surfactant is presented in the formulation in its monomer form.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of 77KS as a bioactive excipient in the NP formulation was based on our previous studies, which showed its pH-sensitive membrane-disruptive activity, together with improved kinetics in the endosomal pH range and low cytotoxic potential (Nogueira et al 2011a(Nogueira et al , 2011b. 77KS was incorporated into the NPs at a concentration below its CMC, thereby indicating that this surfactant is presented in the formulation in its monomer form.…”
Section: Resultsmentioning
confidence: 99%
“…We chose the in vitro model systems to perform this study, as they provide a rapid and effective means to assess NPs for a number of toxicological endpoints and mechanism-driven responses. Primarly, we evaluated if the unloaded-CS-NPs have any cytotoxic effect, which can be attributed especially to the presence of surfactant (Nogueira et al 2011b). Fig.…”
Section: In Vitro Assessments Of Antitumor Activitymentioning
confidence: 99%
“…Naringenin (5) Luteolin (6) Quercetin (7) Vitexin (R= glucose) (8) Quercetin 3-O-β-glucoside (R=glucose) (9) Rutin (10) (Sardari et al, 2009), some of them from the Moraceae family. It is already reported that the cytotoxicity potential of compounds varies with the type of cell line and the method employed to evaluate it (Nogueira et al 2011), also with the type of substance which is investigated and its time of exposition (Van de Sandt, 1992). The screening of anti-HSV-1 activity of the extract was carried on at the highest non-toxic concentration (119 µg/mL) in Vero cells, because being the viruses intracellular parasites, the death of the cells could lead to a false antiviral effect.…”
Section: Antibacterial Assaymentioning
confidence: 99%
“…Specific responses related to the cell line tested are described in the literature with different materials. 31 It is possible to infer that for CCD 1059sk cells derived from skin fibroblasts, latex C-serum was not cytotoxic at the concentrations tested. Although more studies of pre-clinical and clinical toxicity are needed, this results can be an indicative of possible therapeutic application of latex C-serum as a treatment for skin diseases related to reactive species or even preventive skin pharmacological formulations.…”
Section: Discussionmentioning
confidence: 92%
“…11,12 Nogueira et al (2011) 31 recommend that different cell lines from different origins must be used to screen the toxicological effects of new products with potential biomedical applications. For initial screening of latex C-serum potential toxicity, two human cell lines were chosen: MRC-5, derived from lung fibroblasts, and CCD 1059sk, derived from skin fibroblasts.MRC-5 cell line that were exposed to latex C-serum up to the concentration of 50 µg/mL showed no reduction of the cell viability, when compared to the control group.…”
Section: Discussionmentioning
confidence: 99%